Enhancing the Peroxygenase Activity of a Cofactor‐Independent Peroxyzyme by Directed Evolution Enabling Gram‐Scale Epoxide Synthesis. Issue 59 (26th August 2022) - Sigmund, Marie‐Cathérine; Xu, Guangcai; Grandi, Eleonora; Poelarends, Gerrit J.
Abstract: Peroxygenases selectively incorporate oxygen into organic molecules making use of the environmentally friendly oxidant H2 O2 with water being the sole by‐product. These biocatalysts can provide 'green' routes for the synthesis of enantioenriched epoxides, which are fundamental intermediates in the production of pharmaceuticals. The peroxyzyme 4‐oxalocrotonate tautomerase (4‐OT), catalysing the epoxidation of a variety of α, β‐unsaturated aldehydes with H2 O2, is outstanding because of its independence from any cost‐intensive cofactor. However, its low‐level peroxygenase activity and the decrease in the enantiomeric excess of the corresponding α, β‐epoxy‐aldehydes under preparative‐scale conditions is limiting the potential of 4‐OT. Herein we report the directed evolution of a tandem‐fused 4‐OT variant, which showed an ∼150‐fold enhanced peroxygenase activity compared to 4‐OT wild type, enabling the synthesis of α, β‐epoxy‐aldehydes in milligram‐ and gram‐scale with high enantiopurity (up to 98 % ee) and excellent conversions. This engineered cofactor‐independent peroxyzyme can provide new opportunities for the eco‐friendly and practical synthesis of enantioenriched epoxides at large scale. Abstract : Directed evolution of the cofactor‐independent peroxyzyme 4‐OT yielded an efficient biocatalyst (fused 4‐OT P8a) for the enantioselective epoxidation of α, β‐unsaturated aldehydes using hydrogen peroxide as an oxidant. The optimized peroxyzyme enabled the milligram‐ and gram‐scale preparation of the desired α, β‐epoxy‐aldehydes with excellent conversions and outstanding enantiopurity, providing an attractive route towards the synthesis of valuable intermediates for the production of pharmaceuticals.